The role of individual differences in promoting front liners to become customer oriented: A case of the hotel industry in Malaysia - Mohd Noor, Nor Azila; Kasim, Azilah; Scarlat, Cezar; Muhamad, Azli (Taylor & Francis Group, 2012)
As other service industry, hoteliers are highly relying on their contact employees known as front liners to deliver services to customers.Therefore, the behaviors of front liners can influence customers' perceptions of a hotel service. Customer-orientation behavior of employees has become a prime variable of interest for organizations wishing to successfully market their products.However, previous researches on this area have stressed the need for a better understanding of the process relating to customer orientation behavior and its influencing factors.This paper investigates the influence of organizational commitment, self-efficacy and intrinsic job motivation of front liners on customer-orientation behavior.